1963
DOI: 10.1192/bjp.109.461.523
|View full text |Cite
|
Sign up to set email alerts
|

Overinclusive Thought Disorder in Chronic Schizophrenics and its Response to ‘Proketazine’

Abstract: Studies using objective tests have found that two relatively independent types of thought disorder occur in patients diagnosed as “schizophrenic”. In several studies (Payne, 1961) approximately half the acute schizophrenic patients showed an extreme degree of intellectual and motor retardation, more severe than that found even among retarded depressed patients, while half suffered from overinclusive thinking, as measured by the tests used. There was a significant tendency in one study (Payne and Hewlett, 1960)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
1

Year Published

1966
1966
1990
1990

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 6 publications
1
14
1
Order By: Relevance
“…The results also throw doubt on the rationale for Payne's practice of summing converted scores based on a proverbs-test word count and number of object-sorting items selected as a partial definition of overinclusion (Payne & Friedlander, 1962;Payne et al, 1963). Since the r's between these variables are very low (.007 in the present paper and -.030 in a population studied by Hawks, 1964), it would seem that the practice is without empirical justification.…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…The results also throw doubt on the rationale for Payne's practice of summing converted scores based on a proverbs-test word count and number of object-sorting items selected as a partial definition of overinclusion (Payne & Friedlander, 1962;Payne et al, 1963). Since the r's between these variables are very low (.007 in the present paper and -.030 in a population studied by Hawks, 1964), it would seem that the practice is without empirical justification.…”
Section: Resultscontrasting
confidence: 52%
“…Number of Goldstein object-sorting stimuli included was employed on the assumption that this, too, would reflect inability to exclude unnecessary stimuli from a concept. The Payne definitions of overinclusion have also been used extensively in research work on schizophrenic thinking (Payne, Caird, & Laverty, 1964;Payne & Friedlander, 1962;Payne, Friedlander, Laverty, & Haden, 1963;Payne & Hewlett, 1960;Payne, et al, 1959).…”
mentioning
confidence: 99%
“…The effect of phenothiazines on memory tasks (Koh & Kayton, 1974;Koh et al, 1973) and on overinclusion (Payne, Friedlander, Laverty, & Haden, 1963) has been found to be minimal. Hence, patient medication was not controlled.…”
Section: Subjectsmentioning
confidence: 92%
“…The question of medication has been inconsistently tackled in previous studies of overinclusion. Some failed to take it into account (Foulds et al, 1967;Andreasen and Powers, 1974) while others, who did recognize the importance of a drug-free interval, either failed to specify it (Payne et al, 1972) or used an inadequate interval (Payne et al, 1963). A previous study of the effects of phenothiazines on overinclusive thinking, measured by performance on a proverbs test (Chapman et al, 1975) found that overinclusiveness was reduced in some patients (though increased in others) by drug withdrawal.…”
Section: Discussionmentioning
confidence: 94%